2004
DOI: 10.1161/01.res.0000129179.66631.00
|View full text |Cite
|
Sign up to set email alerts
|

Small Heat-Shock Protein Hsp20 Phosphorylation Inhibits β-Agonist-Induced Cardiac Apoptosis

Abstract: Abstract-Activation of the sympathetic nervous system is a common compensatory feature in heart failure, but sustained ␤-adrenergic activation induces cardiomyocyte death, leading to cardiac remodeling and dysfunction. In mouse cardiomyocytes, we recently reported that prolonged exposure to ␤-agonists is associated with transient increases in expression and phosphorylation of a small heat-shock protein, Hsp20. To determine the functional significance of Hsp20, we overexpressed this protein and its constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
144
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(155 citation statements)
references
References 40 publications
(35 reference statements)
9
144
1
1
Order By: Relevance
“…It has also been reported that acute expression of HSP20 in rat cardiomyocytes is protective against apoptosis (20). However, the exact mechanism of HSP20 underlying apoptosis of HCC remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that acute expression of HSP20 in rat cardiomyocytes is protective against apoptosis (20). However, the exact mechanism of HSP20 underlying apoptosis of HCC remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Overexpression of Hsp20 was associated with cardiac protection from ischemia/reperfusion-induced injury and reduced myocardial infarction-mediated apoptosis, 15 consistent with the protective effects of Hsps in the adaptive responses of the heart to physiological/pathophysiological stress. 16,17 Furthermore, adenoviral-mediated overexpression of Hsp20 in isolated adult rat cardiomyocytes revealed inhibition of ␤-adrenergic-induced apoptosis.…”
mentioning
confidence: 79%
“…16,17 Furthermore, adenoviral-mediated overexpression of Hsp20 in isolated adult rat cardiomyocytes revealed inhibition of ␤-adrenergic-induced apoptosis. 12 To determine whether Hsp20 may mediate an in vivo feedback mechanism by which ␤-adrenergic signaling regulates its own subcellular-axis, we used a transgenic (TG) mouse model with cardiac overexpression of Hsp20 and delineated the mechanisms underlying ␤-agonist-induced cardiac remodeling. Our findings indicate that increased sympathetic drive is associated with activation of the cardiac ASK1 cascade, leading to cardiac hypertrophy and heart failure, whereas increased Hsp20 expression attenuates cardiac remodeling and prevents further deterioration, apoptosis, and fibrosis, because of its downregulation of the ASK1-JNK/p38 pathway.…”
mentioning
confidence: 99%
“…Mitogen activated protein kinase activated protein (MAPKAP) kinase-2 is responsible for Hsp27 phosphorylation at all three sites [125,126]. In addition to Ac, Bc and Hsp27, phosphorylation is also common to other sHsps such as Hsp20 [127,128] and occurs readily in all tissues. Phosphorylation of Hsp20 occurs at Ser16 and is mediated by cyclic nucleotide-dependent protein kinases [129].…”
Section: Phosphorylationmentioning
confidence: 99%